Severe Congenital Hypoprothroinbinemia in a Negro Boy - Pool, Judith G.; Desai, Rajendra; Kropatkin, Mona (Thrombosis and Haemostasis, 1962)
A case of severe congenital hypoprothrombinemia (level ca. 3%), complicated only by a moderate deficiency of factor VII (level ca. 45%) is reported in a 6 year old Negro boy.